A PATOP Study of Philosophy and Business Management: Western vs. Chinese Business Structures in Taiwan - Ken Huang, Leelien (Socio-Cultural Management Journal, 2021)
Introduction. Alignment between the philosophical value of the Western parent company and the structure of the local organization is essential to improve managing effectiveness and worker productivity. The alignment may need adjustment while considering whether a Western model is fitted into the Chinese workgroup. This study examines the philosophical value concerning business management within an organization and then explores which value is applicable to the modern Chinese structure in the context of Taiwan. Purpose and methods. The purpose is the holistic view of the Chinese model, as opposed to the separated approach of the West. It does not attempt to find the best philosophical framework of business management for local Chinese structure in Taiwan, as such a framework probably does not exist. Instead, it explores the specific phenomena considered during the process of emergence of business management framework when comparing philosophical value for both selected cases of Western and Chinese enterprises. The case study and PATOP model were used. Results. As a result, there has no single model that is absolutely appropriate to both business and people in one way or the other. Both Chinese and Western philosophical ways of doing business have merits and weaknesses, as illustrated. The implication of the results is the emerged PATOP model. The model indicates an ideal work environment where the Western approach is applicable to the Chinese structure in Taiwan. Conclusions. It concludes that the philosophical approach in doing business within the Chinese structure is erected in a way of “Middle of the Road” according to the PATOP emerged from the study. However, it should be noted that there will be drift as this emerged PATOP model used in the Chinese structure with western approach, indicating another issue “what an acceptable time for drift would be”?